Fibula Nail Outcomes in Soft Tissue Compromised Ankle Fractures. Issue 4 (November 2022) - Ahmed, Maryam; Barrie, Andrew; Kozhikunnath, Arun; Thimmegowda, Abliash; Ho, Sebastian; Kunasingam, Kumar; Guryel, Enis; ,
Category: Trauma; Ankle Introduction/Purpose: Lower limb fractures account for a third of all orthopaedic injuries of which 22% are ankle fractures. With a gradual move toward minimally invasive surgery for ankle fractures, intramedullary implants have evolved over the years to dedicated fixation devices for fibula fractures. The aim of this study was to determine the clinical outcomes following fibula nail fixation and to identify the indication for the use of fibula nails in ankle fractures. Methods: A retrospective study of adult patients from 2 major trauma centers (MTCs) and 9 trauma units (TUs) who underwent fibula nail fixation for AO/OTA 44 fractures between January 1, 2018, and October 31, 2020 was conducted. Fracture were classified based on the Weber or AO/OTA classification. Operative fixation was performed using the Acumed Fibula Rod (Acumend Fibula Rod System, Hilsboro, OR, USA) and a minimally invasive direct approach to the lateral malleolsus with radiography-guided percutaneous screw insertion was used in all patients. The outcome measures included infection, metalwork complications, nonunion or malunion, time to union, and length of inpatient hospital stay. Results: Ninety-five patients were included, with a mean age of 66 years; 57.9% of patients were female. The average body mass index was 30. Sixty-nine patients (72.6%) sustained a Weber B and 24 (27.4%) sustained a Weber C fracture. In addition, 26.3% were open fractures and all patients had soft tissue compromise affecting the lateral malleolus. The calculated infection rate for fibula nail was 4.2% and metalwork complication rate was 5.2%. The nonunion and malunion rate was 8.4% and rate of removal of hardware was 2.1%. The average time to union was 12.5 weeks, and length of inpatient stay was 9.4 days (SD 10). Conclusion: This is the largest multicenter to date which demonstrates that use of a fibula nail appears to be a safe approach to treating patients who have a physiologically higher risk of surgery, poor skin condition, and a complex fracture pattern. The risks of wound and metalwork complicatons appear relatively low following fibula nail fixation in comparison to ankle ORIF's.